Improving Student Learning Outcomes Through the Teaching at the Right Level (TaRL) Approach in the Pancasila Education Subject at SMA Negeri 1 Palembang - Sundari, Nona; Camellia, Camellia; Maimun, Maimun (Jurnal Profesi Pendidikan, 2025)
This research is a Classroom Action Research (CAR) aimed at improving student learning outcomes through the Teaching at The Right Level (TaRL) approach in the Pancasila subject at SMA Negeri 1 Palembang. The subjects of this classroom action research were the students of class XI.2, totaling 38 students. The instrument used in this research was the students’ knowledge test scores to determine the improvement in learning outcomes across three cycles, from cycle one to cycle three. The classroom action research was conducted over three cycles, each consisting of several stages: planning, implementation, observation, and reflection, with each cycle held once per meeting. Data collection techniques involved written tests assessing students’ knowledge in a qualitative descriptive form. The improvement in students’ learning outcomes was obtained from the assessment results after each cycle. The conclusion of this study is that the implementation of the Teaching at The Right Level (TaRL) approach effectively improved student learning outcomes, evidenced by the classical completeness scores of 60% in cycle one, 78% in cycle two, and 97% in cycle three, showing continuous improvement according to the classical completeness criteria.